INVESTIGATING PRE-SERVICE TEACHERS' REFLECTIVE TEACHING PRACTICE IN EFL CLASSROOM INSTRUCTIONAL CONTEXT - Istihari, - (2017)
This research aimed at descriptively investigating pre-service teachers' reflective teaching practice. The contents regarding analysis of the elements of reflection were referred to the notion of reflective teaching proposed by Loughran (2006;1996) and Dewey (1933) and pedagogical knowledge base in ELT by Akbari & Dadvand (2011). Four participants of EFL pre-service teacher doing teaching practice in two state secondary schools were involved in this study. Employing a case study design, data were collected through the participants' reflective teaching journals and semi-structured interviews and were analyzed through inductive thematic analysis from Boyatzis (1998). The overall findings indicated that the all elements of reflection were identified in the pre-service teachers' reflective teaching journals although those elements did not emerge in sequence. Furthermore, the results showed that the issues that rose during teaching practice were related to learning management, knowledge management, classroom management, and language management. It is hoped that this study gives insight to the current debate concerning with the rise of reflective teaching practice related to individual reflection during teaching practice and bring the betterment in teacher education. ----Penelitian ini bertujuan untuk mendeskripsikan secara seksama praktik pengajaran reflektif guru praktikan. Isi mengenai analisis elemen refleksi mengacu pada gagasan pengajaran reflektif yang diajukan oleh Loughran (2006; 1996) dan Dewey (1933) dan basis pengetahuan pedagogik oleh Akbari & Dadvand (2011). Empat peserta guru pre-service EFL yang melakukan praktik mengajar di dua sekolah menengah negeri dilibatkan dalam penelitian ini. Dengan menggunakan desain studi kasus, data dikumpulkan melalui jurnal pengajaran reflektif peserta dan wawancara semi terstruktur dan dianalisis melalui analisis tematik induktif dari Boyatzis (1998). Temuan keseluruhan menunjukkan bahwa semua elemen refleksi teridentifikasi dalam jurnal pengajaran reflektif guru praktikan meskipun elemen-elemen tersebut tidak muncul secara berurutan. Selanjutnya, hasil penelitian menunjukkan bahwa isu yang meningkat selama praktik mengajar terkait dengan manajemen pembelajaran, manajemen pengetahuan, manajemen kelas, dan manajemen bahasa. Diharapkan bahwa penelitian ini memberi wawasan tentang perdebatan saat ini mengenai praktik pembelajaran reflektif yang berkaitan dengan refleksi individu selama praktik mengajar dan membawa kemajuan dalam pendidikan guru.